MEASUREMENT OF RESTAURANT SERVICE QUALITY USING MODIFICATION METHOD OF SERVICE QUALITY AND IMPORTANCE PERFORMANCE ANALYSIS - Putri, Hidayatul Saskya; Shofa, Mohamad Jihan; Ramayanti, Gina (International Journal of Multidisciplinary Research and Literature, 2022)
The purpose of this study is to determine the quality of services provided through customer satisfaction and determine the priority of attributes for improvement. In this study, the modification of Service Quality with 9 dimensions is used (Tangible, Reliability, Responsiveness, Assurance, Empathy, Cleansliness, Health, Safety and Environment Sustainability) and Importance Performance Analysis (IPA). Assessment of service level is given using a questionnaire of 100 samples from customer of sate tegal restaurant in Cilegon City, Banten. This restaurant does not only provide satay culinary, but also provides a variety of other food and beverage culinary menus. The results of the study using the Modified Service Quality Gap method resulted in a negative value, it states that the services provided by restaurants do not provide satisfaction to customers. In an effort to increase customer satisfaction with the services provided by using the Importance Performance Analysis (IPA) method, in quadrant A (top priority) there are 4 service quality attributes that are included in the top priority and must be improved